2020
DOI: 10.1111/dth.13778
|View full text |Cite
|
Sign up to set email alerts
|

Severity and risk ofCOVID‐19 in cancer patients: An evidence‐based learning

Abstract: The immune system of cancer patient gets compromised because of cancer therapy, surgery, and malignancy and thus the probability of infection are increased than the general patients. Immunosuppression can expose cancer patients to serious complications which can lead to delay in diagnosis and unnecessary hospitalizations that may adversely affect the prognosis of the disease. Patients who received chemotherapy or surgery within the 30 days before novel coronavirus disease pandemic have more risk of infection t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Several studies have reported a higher risk of COVID‐19 infection and induced complications in patients with cancer. 4 In response to both this higher vulnerability of patients with cancer to COVID‐19 and the lockdown measures, guidelines were issued to adjust oncologic care during the COVID‐19 pandemic. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 This led to frequent delays and disruptions in cancer health care.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a higher risk of COVID‐19 infection and induced complications in patients with cancer. 4 In response to both this higher vulnerability of patients with cancer to COVID‐19 and the lockdown measures, guidelines were issued to adjust oncologic care during the COVID‐19 pandemic. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 This led to frequent delays and disruptions in cancer health care.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Oncologists hold different notions and continue to receive mixed messages regarding whether cancer patients should receive anti-tumor treatments as usual. [17][18][19] In light of this, a systematic review is needed to summarize the best available evidence of the impact of anti-cancer therapy in cancer patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…According to Lee et al cancer patients are twice more likely to contract the infection than the normal population (Lee et al, 2020 ). Patients who received chemotherapy or surgery within the 30 days before the COVID-19 pandemic have more risk of infection than the patients who had not undergone chemotherapy or surgery (Sharma et al, 2020 ). According to an analysis of Italian patients published in March, 20% of those who died from COVID-19 in the country had active cancer (Liang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%